Blockchain based E-procurement system to eradicate corruption in public sector - Tajrin, Rabana; Tasnia, Lubaba; Masiat, Shabab; Rahman, Md. Alkawser (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.